HOW SOON THE ENVIRONMENTAL PERFORMANCE CAN CREATE FIRM'S VALUE IN ASIA - Althaf Syah Abdali; Ancella Anitawati Hermawan (Widya Mandala Surabaya Catholic University, 2025)
Research Purposes. This study aims to investigate the effect of Environmental performance on the financial performance of companies in sectors sensitive to natural issues in Asia, for the current year, the following year, and two years after. Research Methods. The study employs quantitative methods, utilizing secondary data and regression analyses. Research Results and Findings. The results of this study indicate that environmental performance has a significant negative impact on financial performance, and the moderating variable of Women on Board does not strengthen the relationship between environmental performance and financial performance. This outcome may be attributed to the costs of improving environmental performance not being commensurate with their impact on financial performance. Furthermore, the influence of women on boards may be limited because there may not be many strategic positions within these companies held by women. The implications of these findings are to provide guidance for corporate decision-making in addressing sustainability issues through corporate financial performance, while still maximizing the financial performance of companies, particularly in Asian firms sensitive to natural resource issues.